The Ideophone in Siswati - Matfunjwa, Muzi; Nkuna, Khulisile Judith (Forum for Linguistic Studies, 2025)
South Africa is a multilingual country wherein 12 languages are official, including Siswati. As in other Bantu languages, the ideophone is a unique part of speech in Siswati that is predominantly used by language users in daily conversations for various communicative purposes. Despite the wide use of the Siswati ideophones, few scholars have investigated them in depth from different perspectives. Therefore, this article describes the features of the ideophone in Siswati from phonological, morphological, semantic and syntactic perspectives. The investigators used convenience sampling as a method of collecting data. This data was obtained mainly from various Siswati literary works, which are a true representation of the language usage, supplemented by native speakers’ intuition. The prototype theory and the systematic functional linguistics approach mainly underpin this study. The gathered corpora were systematically explored to determine the phonological features of ideophones, their use in sentence construction, and the meanings they convey in various contexts. The ideophones were classified based on their syllables and formation, as well as their semantic functions.This study is significant as it brings useful insights into the nature of ideophones in Siswati and contributes to the existing body of knowledge in the language. The results show that even though formal speech lacks ideophones, this part of speech is frequently used in normal day-to-day conversations in Siswati to fulfil various linguistic needs.